(untitled) (European Journal of Behavioral Sciences, 2020)
No matter how bizarre and unreal myths may be they embody extraordinary power and influence. Undoubtedly, myths also possess some measure of historical authenticity. One of the first women in western history to be cloaked in the mantle of fame and mystery was Mary Magdalene. She emerges as a semi-mythical figure. However, judging by the spiritual message of love she instils into the hearts of millions of Christian believers, and by viewing the thousands of works of art evoking her supposed attributes, deeds and influence, and in surveying the numerous churches, convents and other religious orders erected in her honor as their patron saint, one can say that her shadow bridges the divide between myth and history. In my research I find it doubtful whether the disciples would have had the courage to continue advancing the cause of Christianity without Mary. in the wake of Christ’s death, Christianity sank to its lowest point; and would either have vanished or become just another marginal Jewish sect. It was due to Mary’s charisma and fortitude that empowered Christianity with the tools to persevere. The Magdalene phenomenon lingered on as a growing threat to the Church. How else can we explain the extreme measures the Church eventually took in expunging her memory? Branding the Magdalene myth with sin aided in negating the gender equality ethos of the early apostolic church and justifying the authorization of the Petrus pope dynasty.